Implementation of Quality Improvements to Minimize Critical to Quality Variations in Polyurethane Liquid Injection Processes - Nazaruddin Nazaruddin (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
PT Topjaya Antariksa Electronics is a manufacturing company that produces various refrigerators, home freezers, and showcase refrigerators. Refrigerators are produced in the form of single doors and twin doors. This company was founded in 1988 and distributed by Toshiba Sarana Utama throughout Indonesia. This research is intended to reduce the process failure rate so that the potential for defects produced in the polyurethane shop is reduced by finding repair solutions. This study aims to plan improvement efforts to reduce process failures in the polyurethane shop and then evaluate the results of implementing the proposal. The FMEA (Failure Mode and Effect Analysis) method is used. This method performs several stages, such as determining the potential failure mode in each process, identifying the cause of failure, and then making a priority order. Process failure in this polyurethane shop is the most significant process failure compared to other shops. This failure causes the defects in the process at the polyurethane shop to be higher than in other shops. In 2019, 2020, and 2021, the number of refrigerator cabinets in the flawed polyurethane injection process amounted to 7,666 units, 8,256 units, and 8,014 units. The percentage of defects compared to the amount of production found in the polyurethane injection process each year was 18.46%, 17.82%, and 18.11%.